2019
DOI: 10.18632/oncotarget.27215
|View full text |Cite
|
Sign up to set email alerts
|

Splicing regulatory factors in breast cancer hallmarks and disease progression

Abstract: By regulating transcript isoform expression levels, alternative splicing provides an additional layer of protein control. Recent studies show evidence that cancer cells use different splicing events to fulfill their requirements in order to develop, progress and metastasize. However, there has been less attention for the role of the complex catalyzing the complicated multistep splicing reaction: the spliceosome. The spliceosome consists of multiple sub-complexes in total comprising 244 proteins or splice facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 165 publications
(183 reference statements)
0
17
0
Order By: Relevance
“…Further, we identify a IPO9 , a nuclear actin transporter, implicated in mRNA metabolism and alternative splicing, as a putative oncogene in breast cancer, melanoma, bladder cancer, and mesothelioma. In addition to IPO9 , other newly identified regulatory driver genes, including SRSF2 and TCERG1 , also modulate alternative splicing (Koedoot et al, 2019;Montes et al, 2015;Pearson et al, 2008) , suggesting a shared functional basis for these enrichments, similar to that also seen for alternative splicing in coding mutations (Watson et al, 2013) .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Further, we identify a IPO9 , a nuclear actin transporter, implicated in mRNA metabolism and alternative splicing, as a putative oncogene in breast cancer, melanoma, bladder cancer, and mesothelioma. In addition to IPO9 , other newly identified regulatory driver genes, including SRSF2 and TCERG1 , also modulate alternative splicing (Koedoot et al, 2019;Montes et al, 2015;Pearson et al, 2008) , suggesting a shared functional basis for these enrichments, similar to that also seen for alternative splicing in coding mutations (Watson et al, 2013) .…”
Section: Discussionmentioning
confidence: 76%
“…In addition, nuclear actin dynamics, mediated by IPO9 and XPO6 , have the potential to modulate mRNA splicing through disruption of SMN2 (Viita et al, 2019) . Alternative splicing and other co-transcriptional metabolic processes acting on RNA are important for cancer development (David and Manley, 2010;Koedoot et al, 2019) , suggesting a multitude of direct targets in promoting the hallmarks of cancer (Hanahan and Weinberg, 2011) . These diverse roles of nuclear actin in cellular proliferation and transcription are consistent with our findings of mutational enrichment in IPO9 regulatory regions and the association between elevated expression of IPO9 and shorter relapse-free and overall survival in multiple cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies analyzing 4,398 cases with familial breast cancer causes and 4,316 controls identified five single-nucleotide polymorphisms of FGFR2 significantly associated with breast cancer 36 . SRPK1 is a serine/arginine-rich protein-specific kinase and one of the core splicing factors 37 ; it is highly expressed in more aggressive basal breast cancer. High expression levels of SRPK1 correlated with low metastasis-free survival in patients with ER-positive, but not ER-negative, breast cancer 38 .…”
Section: Resultsmentioning
confidence: 99%
“…(1) As the AS is a critical component of the regulation of gene expression pathways, how the detailed mechanisms and regulation of alternative pre-mRNA splicing should be elucidated. (2) Since many splice factors are involved in multiple hallmarks of diseases, 46 investigation on these factors might provide a new layer of disease treatment or a potential method to combat disease progression. (3) Why different transcripts perform different functions?…”
Section: Discussionmentioning
confidence: 99%